Design and Implementation of an IoT-based Transactional System for Quality Management - Younis, Mohammed Issam; Alwan, Athraa H. (Iraqi Journal of Science, 2021)
The spread of Coronavirus has forced populations around the globe to adopt strict measures such as lockdown, home quarantine, and home office. Moreover, in the current development of network communications, people can exploit internet and intranet features in many systems that need to be faster, more efficient, and available on time. Furthermore, with the benefits of using internet-of-things (IoT), through which things are generated, gained, discovered, and proposed without interference, the user could receive the last status without exertion and direct contact (i.e., in a contactless manner). These specifications can be used in a transaction system. This paper proposes an electronic transaction system (ETS) as a replacement for the current paper transaction used in most organizations’ environments. The progress includes the signing privilege, access right for each position, delivery reports, transaction tracking, and transaction storage safety. Transactions will be stored in an encrypted way at the database to keep them safe from illegal changes. For that, a secure electronic transaction is created with digital signature services. The negligence can be identified in the workflow by tracking the operations and receiving exceptional cases’ alerts. Finally, this paper compared the proposed system against state-of-the-art systems.